1997
DOI: 10.1046/j.1365-2796.1997.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with ischaemic heart disease: a prospective controlled study

Abstract: Abstract. Westin L, Carlsson R, Israelsson B, Willenheimer R, Cline C, McNeil TF (University of Lund, University Hospital, Malmö, Sweden). Quality of life in patients with ischaemic heart disease: a prospective controlled study. J Intern Med 1997; 242: 239-47.Objectives. To assess quality of life in patients after acute myocardial infarction (AMI), coronary artery by-pass grafting surgery (CABG) and percutaneous transluminal coronary angioplasty (PTCA) as compared with healthy controls. Design. Self-administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
44
3
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 23 publications
(25 reference statements)
7
44
3
6
Order By: Relevance
“…The overall quality of life (QL) comprises all factors which influence on someones health and health-related quality of life (HRQL) comprises only those factors which are the part of someone's health [3,4]. AMI has negative consequences on the HRQL of the patients and that leads to the lowering of their HRQL even several years after the AMI [6][7][8][9].During the first month after the AMI patients are very vulnerabile physically, mentally and emotionally [10]. According to the results of investigations it was determined that HRQL among the patients was disordered and lower and the main reason for that was the presence of the chest pain or discomfort and the lowering of the overall physical function [11][12][13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The overall quality of life (QL) comprises all factors which influence on someones health and health-related quality of life (HRQL) comprises only those factors which are the part of someone's health [3,4]. AMI has negative consequences on the HRQL of the patients and that leads to the lowering of their HRQL even several years after the AMI [6][7][8][9].During the first month after the AMI patients are very vulnerabile physically, mentally and emotionally [10]. According to the results of investigations it was determined that HRQL among the patients was disordered and lower and the main reason for that was the presence of the chest pain or discomfort and the lowering of the overall physical function [11][12][13].…”
mentioning
confidence: 99%
“…AMI has negative consequences on the HRQL of the patients and that leads to the lowering of their HRQL even several years after the AMI [6][7][8][9].…”
mentioning
confidence: 99%
“…3 Studies of patients with myocardial infarction have measured the effect of illness and interventions on HRQL. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Many of these studies are conducted in the context of controlled clinical trials assessing the effectiveness of an intervention. In health services research, in which the focus of measurement is typically the process of care, ongoing measurement of patient-reported health status provides a way to move from measuring process outcomes to improving care for groups and individual patients.…”
Section: Registry Patientsmentioning
confidence: 99%
“…The influence of the residual effects of acute myocardial ischemic events on patients' functional and health status has been the focus of many research studies over the past several decades. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] These studies have identified many patient, disease, and treatment characteristics associated with health status or HRQOL, including the type of ACS event. The present analysis was not able to control for the type of ACS event because of inconsistent documentation in the ACS registry, the source of data for this project.…”
Section: Limitationsmentioning
confidence: 99%
“…[8,[65][66][67][68] Despite this recognition, inequality of care is currently received by patients with coronary heart disease in different social classes and different geographical areas. [2] The gap between rich and poor in respect to levels of heart disease is widening.…”
Section: Social Inequalitymentioning
confidence: 99%